1988
DOI: 10.1007/bf00916553
|View full text |Cite
|
Sign up to set email alerts
|

Sulfidopeptide-leukotriene peptidases in pulmonary edema fluid from patients with the adult respiratory distress syndrome

Abstract: The human pulmonary edema fluid concentrations of LTC4 and of LTD4 and LTE4, derived peptidolytically from LTC4, were assessed by radioimmunoassays of the mediators resolved by reverse-phase high-performance liquid chromatography. The mean pulmonary edema fluid concentration (+/- SD) of LTD4 of 19.2 +/- 25.6 nM for 12 patients with the adult respiratory distress syndrome and of LTE4 of 192 +/- 309 nM for 10 of the patients were significantly higher (P less than 0.005 and P less than 0.05) than those of 2.2 +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…As a starting point, we investigated eicosanoids derived from the cyclooxygenase (COX) pathway. Our working hypothesis was that some COX metabolites would be increased, considering that IL-1β levels are elevated in the BALs of some COVID-19 patients (16) Leukotrienes are also potent bioactive lipids previously documented to regulate the inflammatory responses in the airway/lung in diseases, notably ARDS (20,21). As such, their involvement in the pathogenesis of COVID-19 has recently been postulated even though their levels were unknown (22).…”
Section: Resultsmentioning
confidence: 99%
“…As a starting point, we investigated eicosanoids derived from the cyclooxygenase (COX) pathway. Our working hypothesis was that some COX metabolites would be increased, considering that IL-1β levels are elevated in the BALs of some COVID-19 patients (16) Leukotrienes are also potent bioactive lipids previously documented to regulate the inflammatory responses in the airway/lung in diseases, notably ARDS (20,21). As such, their involvement in the pathogenesis of COVID-19 has recently been postulated even though their levels were unknown (22).…”
Section: Resultsmentioning
confidence: 99%
“…LT concentrations have been reported to be elevated in other experimental models of acute lung injury (22,27). Moreover, increased levels of LTs have been detected in pulmonary edema fluid obtained from patients with ARDS (23)(24)(25). LTs are primarily synthesized by activated cells of myeloid origin, such as neutrophils, eosinophils, mast cells, and monocytes/macrophages (26).…”
Section: Discussionmentioning
confidence: 99%
“…LTs have been implicated as inflammatory mediators in experimental models of acute lung injury (22) and were found to be elevated in pulmonary edema fluid obtained from patients with ARDS (23)(24)(25). Moreover, cysLTs appear to play a critical role in mediating neutrophil-dependent inflammation (26).…”
mentioning
confidence: 99%
“…However, this injury was not consistent, and it was considered that the bronchial clearance of 99mTcDTPA constitutes a large enough portion of total pulmonary clearance to be responsible for the increase in 99-TcDTPA lung uptake observed in the SSCS rabbits. Many investigators have demonstrated that sulfidopeptide leukotrienes, mainly LTC4 and LTD4, can increase vascular permeability [17][18][19][20]; but the possibility that LTE4 can also cause increased permeability in alveolar epithelial cells cannot be dismissed.…”
Section: Discussionmentioning
confidence: 99%